1993
DOI: 10.4049/jimmunol.151.8.4286
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of major heat shock protein hsp70 inhibits tumor necrosis factor-induced activation of phospholipase A2.

Abstract: We have recently shown that major heat shock protein (hsp70) protects WEHI-S tumor cells from the cytotoxicity mediated by TNF. In the present study, the mechanism of hsp70-associated TNF resistance was investigated. Overexpression of human hsp70 or inhibition of endogenous hsp70 synthesis by expression of antisense hsp70 RNA did not change the ability of WEHI-S tumor cells to bind TNF or internalize and degrade the receptor-bound TNF. Moreover, TNF-induced activation of NF-kappa B-like transcription factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the human endometrium, HSPs act as protective agents against cytotoxic damage caused by cytokines such as TNFA (Tabibzadeh & Broome, 1999). Furthermore, HSPs prevent or arrest inflammatory damage by promoting the production of anti‐inflammatory cytokines with immunoregulatory effects (Jäättelä, 1993; Jäättelä et al., 1992; van Eden et al., 2005; Wieten et al., 2007). We found that HSP expression was relatively lower in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%
“…In the human endometrium, HSPs act as protective agents against cytotoxic damage caused by cytokines such as TNFA (Tabibzadeh & Broome, 1999). Furthermore, HSPs prevent or arrest inflammatory damage by promoting the production of anti‐inflammatory cytokines with immunoregulatory effects (Jäättelä, 1993; Jäättelä et al., 1992; van Eden et al., 2005; Wieten et al., 2007). We found that HSP expression was relatively lower in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the enzymatic release of arachidonic acid (AA) from membrane phospholipids. PLA 2 activity in TNF‐treated cells was examined by measuring the release of [ 3 H]arachidonic acid into the cell culture supernatants (Jäättelä, 1993). TNF stimulation reproducibly caused the release of AA metabolites from the tested cells (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…TNF increases PLA 2 activity in association with its cytotoxic and mitogenic responses (Palombella and Vilcek, 1989; Jäättelä, 1993). This leads to the enzymatic release of arachidonic acid (AA) from membrane phospholipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many lines of evidence point to constitutively overexpressed Hsp72 as being able to block apoptotic cell death initiated by cellular stress including heat shock, ceramide, ethanol, ionizing irradiation, TNF‐α and ischemia (Jaattela, 1993; Simon et al ., 1995; Bellmann et al ., 1996; Samali and Cotter, 1996; Gabai et al ., 1997; Liossis et al ., 1997; Mosser et al ., 1997; Meriin et al ., 1998; Sharp et al ., 1999). Moreover, Hsp72, when induced in a cellular response to apoptotic stress, exerts an anti‐apoptotic effect in various types of cells (Samali and Cotter, 1996; Gordon et al ., 1997), and it is frequently expressed at higher levels in human cancer cells (Li et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%